G. E. Lessing „Ernst und Falk. Gespräche für Freimäurer" - Hauptpositionen der Rezeption bis 1933 - Dziergwa, Roman (Studia Germanica Posnaniensia, 2018)
The most important evidence of an intensive influence of this outstanding humanistic work of Lessing beyond the free-mason milieu was the creative reception of free-masonic conversations by Herder, Friedrich Schlegel, and Fichte. Already in the early phase of reception this work was used for the radical political goals in the Enlightenment ideology of the Order of llluminates by Adam Weishaupt. Another variant of ideological-political instrumentalization was the revolutionary-socialist reception among the German communists who lived as emigrants in Paris. The fundamental trend of this reception was undertaken and developed by the later Marxist interpreters (Mehring). Ideological one-sidedness of this kind of reception was relativized by the authors of works on the study of literature who presented more varied and balanced opinions.